Causal Evaluation of Pancreatitis in Children (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Pancreatitis in childhood is not common. It can be associated with severe morbidity and mortality. The role of clinical evaluation is vital as it can be misdiagnosed easily. This study was aimed to review the prevalence, etiology, presentation and outcome of pancreatitis in children. This cross-sectional study was conducted at the Department of Pediatric Gastroenterology & Nutrition of Bangabandhu Sheikh Mujib Medical University, Dhaka from January, 2017 through June, 2018. A total 43 cases of pancreatitis were included in this study. Pancreatitis was classified as acute pancreatitis(AP), acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) as per diagnostic criteria made by INSPPIRE (International Study Group of Pediatric Pancreatitis: In Search for a Cure) group. Among 43 children (age 10.1 mean ± 2.55,18 males); AP,14 (32.6%); ARP, 14(32.6%) and CP,15(34.8 %). Half of AP was idiopathic. Majority of ARP (28.6%) were idiopathic and CP (40%) had calcific pancreatitis. Majority of patients had vomiting followed by moderate to severe abdominal pain. In CP 4(26.6%) patient developed diabetes mellitus. Majority of pancreatitis in children is idiopathic. A sub-set of AP goes on to develop ARP and CP on follow-up and being in the idiopathic sub-set is a risk factor. CP is progress to endocrine and exocrine insufficiency. Early diagnosis, close monitoring and proper intervention are mandatory to reduce the potential morbidity and mortality.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):76-79